The hidden microbial ecosystem in the perennial ice from a Pyrenean ice cave - Ruiz-Blas, Fátima; Muñoz-Hisado, Víctor; Garcia-Lopez, Eva; Moreno, Ana; Bartolomé, Miguel; Leunda, Maria; Martinez-Alonso, Emma; Alcázar, Alberto; Cid, Cristina (Frontiers in Microbiology, 2023)
Over the last years, perennial ice deposits located within caves have awakened interest as places to study microbial communities since they represent unique cryospheric archives of climate change. Since the beginning of the 20th century, the temperature has gradually increased, and it is estimated that by the end of this century the increase in average temperature could be around 4.0ºC. In this context of global warming the ice deposits of the Pyrenean caves are undergoing a significant regression. Among this type of caves, that on the Cotiella Massif in the Southern Pyrenees is one of the southernmost studied in Europe. These types of caves house microbial communities which have so far been barely explored, and therefore their study is necessary. In this work, the microbial communities of the Pyrenean ice cave A294 were identified using metabarcoding techniques. In addition, research work was carried out to analyze how the age and composition of the ice affect the composition of the bacterial and microeukaryotic populations. Finally, the in vivo effect of climate change on the cellular machinery that allow microorganisms to live with increasing temperatures has been studied using proteomic techniques.